Fuzzy aggregate production planning by using fuzzy Goal programming with practical application - بخيت, عبد الجبار خضر; كامل, رشا ضاري (Journal of Economics and Administrative Sciences, 2017)
Research summarized in applying the model  of fuzzy goal programming for aggregate production planning , in General Company for hydraulic industries / plastic factory to get an optimal production plan  trying to cope with the impact that fluctuations in demand and  employs all available resources using two strategies where they are available   inventories  strategy and  the strategy of  change in the level of the workforce, these   strategies  costs are usually imprecise/fuzzy. The plant administration trying to minimize total production costs, minimize carrying costs and minimize changes in labour levels. depending on the gained data from the plant of the major products for the second half of 2015 nd after the dissolution of the model using the software (GAMS) was getting the best level from the  production , inventory and  labour levels , where the total production costs was (7041700000) dinar Which is good compared to the cost reduction Cost set by the factory administration, which was (7668442100)dinars a difference (626742100) , carrying costs was  (4327200 ) dinar Which is good compared to the cost reduction Cost set by the factory administration, which was ( 5583400)dinars a difference (1256200) and It found that the factory does not need to hire or lay off workers for the duration of the production plan. And resulting deviational value for the three fuzzy goal ( are (0.938, 1, 1) respectively. Through results we found that deviational value of the goals were close and equal for (1) that  consider good , that were obtained were catered level of ambition of the decision-maker values.